2008
DOI: 10.1002/ejic.200800063
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐Ligand Oxidovanadium(V) Complexes with N′‐Salicylidenehydrazides: Synthesis, Structure, and 51V Solid‐State MAS NMR Investigation

Abstract: Keywords: 8-Hydroxyquinoline / Schiff bases / Square-wave voltammetry / Vanadium / 51 V NMR spectroscopyThe synthesis and spectroscopic characterization of a series of three oxidovanadium(V) complexes with 8-hydroxyquinoline and Schiff-base ligands derived from salicylaldehyde and ω-hydroxy-functionalized carbohydrazides with different chain lengths are reported. The complex with the hydrazone ligand containing the shortest chain length was crystallographically characterized. This complex crystallizes in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 49 publications
(62 reference statements)
0
55
0
Order By: Relevance
“…9, 17, 2325, 52, 53 The derived quadrupolar parameter, CQ1η2/3, takes into account the asymmetry parameter of the EFG tensor as well as C Q and is useful because it can be extracted based solely on the second-order quadrupolar shift. 9 Perhaps not surprisingly, there is no clear trend in these graphs that would provide a useful correlation between the NMR observables and coordination number.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9, 17, 2325, 52, 53 The derived quadrupolar parameter, CQ1η2/3, takes into account the asymmetry parameter of the EFG tensor as well as C Q and is useful because it can be extracted based solely on the second-order quadrupolar shift. 9 Perhaps not surprisingly, there is no clear trend in these graphs that would provide a useful correlation between the NMR observables and coordination number.…”
Section: Resultsmentioning
confidence: 99%
“…28 The biological activity of vanadium complexes and proteins is determined by the specific chemical environment of the vanadium centers. The application of 51 V NMR to study solid vanadium-containing complexes that are of biological relevance has grown rapidly in recent years 925 due to the ability to acquire high quality magic angle spinning spectra of both the central and satellite NMR transitions of the 51 V (I = 7/2). Studies have demonstrated that both the quadrupolar coupling and the chemical shift anisotropy, which can be determined from the solid-state NMR spectra, are sensitive to the local vanadium environment and can be used to understand changes in the local molecular orbital structure and ground state charge distribution at the vanadium.…”
Section: Introductionmentioning
confidence: 99%
“…The potentials reported in this paper refer to the ferrocenium/ferrocene couple, which has been measured at the end of each experiment (for details see ref. [38] ).…”
Section: 4-diamino-n-(4-methoxyphenyl)carbazole (1)mentioning
confidence: 93%
“…1, 15, 3339 A hybrid 51 V SSNMR / Density Functional Theory (DFT) approach provides highly sensitive information regarding electronic structure and geometry not only in coordination complexes 1, 15, 3336, 4144 but also in large proteins, such-as vanadium-containing haloperoxidases. 37 This sensitivity arises from the fact that 51 V is a half-integer quadrupolar nucleus (I=7/2).…”
Section: Introductionmentioning
confidence: 99%